Correction of Ametropia in Patients with Posterior Elevation of the Cornea - E. N. Eskina; V. A. Parshina; M. Kh. Movsesyan; A. V. Malakhova (Oftalʹmologiâ)
Purpose: to evaluate the effectiveness of ametropia correction in patients with posterior corneal elevation but without signs of subclinical keratoconus, based on postoperative results of transepithelial photorefractive keratectomy (Trans PRK).Patients and methods. A retrospective comparative study was conducted to analyze the results of surface ablation, which was performed using transepithelial photorefractive keratectomy in 18 patients with posterior corneal elevation (36 eyes). The control group included 18 patients with eyes without these changes (36 eyes). Both groups were comparable in age, gender and refraction. Demographic data, pre- and postoperative refraction, NCOSIS and ICOSIS, maximum ablation, I/S ratio index, central corneal thickness, anterior and posterior keratometry, Biaocci-Versachi index for anterior and posterior surfaces, RMS (mk/mm2) in standard deviation, the highest elevation point of the posterior surface of the cornea — KVB (microns), index of asymmetry of tangential curvature of anterior and posterior were determined and analyzed in all patients the surfaces are SIF (D) and SIB(D), which determines the vertical asymmetry in the upper and lower hemispheres of the cornea.Results. Observations of the dynamics of these parameters were carried out for 12 months after surgery for patients of both groups, and showed that the conclusion of Trans PRK in patients with posterior corneal elevation leads to similar refractive results compared with normal eyes. The safety and effectiveness indicators for both groups were also comparable. Significant differences in the speed of vision restoration between the groups were revealed, which is manifested by significant differences in visual acuity indicators within 1 month after surgery, but by 1 year the differences are leveled. It was determined that the effectiveness of astigmatism correction in the group with posterior elevation was significantly lower. The refractive results in the elevation group were good. During the observation, there was no pronounced dynamics of the indicators of elevation of the posterior surface of the cornea.Conclusion: the method of transepithelial photorefractive keratectomy can be recommended for the treatment of ametropia in patients with posterior corneal elevation, but without signs of subclinical keratoconus, however, the development of additional nomograms is required in order to increase the predictability of laser vision correction in patients of this category.